2022
DOI: 10.7759/cureus.23437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Profile of 25-Gauge Pars Plana Vitrectomy in Rhegmatogenous Retinal Detachment in Pakistan: A Multicenter Retrospective Study

Abstract: Introduction This study aims to evaluate the primary anatomical success and visual outcomes of 25-gauge pars plana vitrectomy (25g PPV) in patients with rhegmatogenous retinal detachment (RRD) in Pakistan. Design This is a five-year retrospective, interventional cohort study conducted at tertiary care hospitals in Pakistan from October 2013 to October 2018. Methods This is a retrospective, interventional cohort study of 418 consecutive patients with RRD wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, as in literature sources, clinical characteristics of patients are diff erent in our observation. This is because the availability of high-tech ophthalmic care is not the same in individual countries Awan and co-authors [5] in a large-scale observational sample (452 patients) showed that in the majority of patients the detachment involved the macula (77.3%), with severe proliferative vitreoretinopathy (stage C) occurring in 22.7% of cases. In our observation, the results are diff erent, grade C proliferative vitreoretinopathy was recorded in more patients (34.0±4.6%).…”
Section:  Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as in literature sources, clinical characteristics of patients are diff erent in our observation. This is because the availability of high-tech ophthalmic care is not the same in individual countries Awan and co-authors [5] in a large-scale observational sample (452 patients) showed that in the majority of patients the detachment involved the macula (77.3%), with severe proliferative vitreoretinopathy (stage C) occurring in 22.7% of cases. In our observation, the results are diff erent, grade C proliferative vitreoretinopathy was recorded in more patients (34.0±4.6%).…”
Section:  Discussionmentioning
confidence: 99%
“…Examination and treatment of patients diagnosed with retinal detachment is carried out in high-tech institutions (ophthalmology results and university clinics) [5][6][7]. The clinical characteristics of patients in these institutions are diff erent.…”
Section:  Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size was calculated by using Open Epi sample size calculator. Taking statistics of Treatment success(no re-detachment) as 89% 15 at margin of error of 9% and confidence interval of 95%. All the cases were included through non-probability consecutive sampling technique.…”
Section: Methodsmentioning
confidence: 99%